2014
DOI: 10.1371/journal.pone.0092686
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Activator Inhibitor-1 Is Involved in Impaired Bone Repair Associated with Diabetes in Female Mice

Abstract: Previous studies suggest that fracture healing is impaired in diabetes; however, the underlying mechanism remains unclear. Here, we investigated the roles of plasminogen activator inhibitor-1 (PAI-1) in the impaired bone repair process by using streptozotocin (STZ)-induced diabetic female wild-type (PAI-1 +/+) and PAI-1-deficient (PAI-1 −/−) mice. Bone repair and the number of alkaline phosphatase (ALP)-positive cells at the site of a femoral bone damage were comparable in PAI-1 +/+ and PAI-1 −/− mice without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 35 publications
4
46
3
Order By: Relevance
“…Further, we have also demonstrated that the fibrinolytic system is crucial to regulate bone metabolism and repair [9,10,[12][13][14]. In contrast, our current results show that plasmin does not affect expression of IL-1β and TNF-α mRNA in monocytic cells, suggesting that stimulation of these cytokines does not require the fibrinolytic system.…”
Section: Role Of Erk1/2 and P38 Mapk In α 2 -Ap Activitycontrasting
confidence: 55%
See 2 more Smart Citations
“…Further, we have also demonstrated that the fibrinolytic system is crucial to regulate bone metabolism and repair [9,10,[12][13][14]. In contrast, our current results show that plasmin does not affect expression of IL-1β and TNF-α mRNA in monocytic cells, suggesting that stimulation of these cytokines does not require the fibrinolytic system.…”
Section: Role Of Erk1/2 and P38 Mapk In α 2 -Ap Activitycontrasting
confidence: 55%
“…Daci et al revealed that PAI-1 deficiency blunts trabecular bone loss induced by OVX in mice [11]. Our recent study revealed that PAI-1 is involved in diabetic bone loss and delayed bone repair as well as glucocorticoidinduced osteopenia and muscle wasting [12][13][14]. Taken together, the data imply that activation of the fibrinolytic system might regulate bone metabolism in postmenopausal and secondary osteoporosis.…”
Section: Role Of Erk1/2 and P38 Mapk In α 2 -Ap Activitymentioning
confidence: 51%
See 1 more Smart Citation
“…Also, plasma levels of plasminogen activator inhibitor 1 (PAI-1), an inhibitor of fibrinolysis, are generally increased in obese patients and in those with Type 2 diabetes (49). Increased amounts of PAI-1 contribute to reduced plasmin activation and a prothrombotic state, which may promote atherogenesis and increase the risk of CVD (49,72). Conversely, a reduction in plasmin activation is also associated with reduced activation of transforming growth factor-␤ (TGF-␤), a molecule important for suppressing the proliferation and migration of smooth muscle cells that contributes to atherosclerotic lesion formation (71).…”
Section: Overnutrition Obesity and Cardiovascular Diseasesmentioning
confidence: 99%
“…Recently, we investigated the roles of tissue-fibrinolytic systems and the diabetic state on bone healing using the efficient bone repair model after femoral bone damage in mice (16,17,25). Therefore, in the present study, we examined the effects of bone defect on HSCs and MSCs in bone marrow from the damaged femur in mice and tried to clarify their detailed mechanisms using this model.…”
mentioning
confidence: 99%